Knowledge and practices of Primary Health Care professionals on the care of people with Spinal Cord Trauma (Research, Society and Development, 2022)
Objective: to understand the knowledge and practices of Primary Health Care professionals about the care of people with spinal cord trauma. Method: qualitative study conducted with 12 professionals of the Family Health Strategy of the city of Natal, Rio Grande do Norte. Data were collected in December 2020 through a focus group. The data were transcribed and analyzed according to thematic analysis. Results: The research subjects were mostly Catholic women, with complete higher education and mean time of performance in PHC ranging from five to 22 years. And, no history of training for the care of people with TRM. From the statements emerged the following categories: I- The care of the person with Spinal Cord Trauma; II - Needs experienced in the daily life of caring.  Conclusion: the care of people with spinal cord trauma is permeated by structural difficulties, especially lack of training of professionals for comprehensive and multidisciplinary care. We highlight the need for permanent education actions to improve assistance to this clientele.